Confrontations entre jeunes et police en Angleterre et en France - Sophie Body-Gendrot (L'Ordinaire des Amériques)
There is an old history of urban violence in England and France. An analysis of the past thirty years reveals convergences in terms of mobilization, participants, contagion, and responses brought to violence. Globalized economy is involved. Pauperization of the violent sites in the old Fordian neighborhoods, absence of mobility of many youngsters, high structural unemployment in those neighborhoods, political disaffiliation, absence of transmission channels for the population’s demands, tensions with a police force disconnected from the residents, rumors, antagonistic street cultures, policies not suited to those neighborhoods, all these factors partly account for the irruption of violence. There are, however, obvious differences, from one neighborhood to the next, from one decade to the next, from one country to the other, in the form taken by the disorders (for instance looting in England in 2011 or the confrontation of youngsters to the symbols of the state in France), as well in the local and national responses in the two countries (investigation reports in England as a prelude to reforms).